Guía turística de la parroquia Zumbahua, cantón Pujilí, provincia de Cotopaxi. - Lisintuña Umajinga, Iván (2018)
The study area is located in the Zumbahua parish, Pujilí canton, Cotopaxi province, this parish has a great wealth of natural and cultural tourist attractions that if managed in a correct way would be decisive to achieve their tourism development and achieve a positioning to Nacional area. In the first instance, the primary and secondary information was collected to determine the current state of the tourist activity in this parish, in the same way the collection of information necessary for the development of the parish diagnosis, obtaining general, economic, environmental, sociocultural and tourist diagnosis where the 12 attractions to be inventoried and included in the tourist guide. In order to generate the inventory of attractions as well as accommodation and food establishments, the MINTUR cards were applied. For the attractions, the files for the survey and ranking of tourist attractions were used to generate relevant information on each of the attractions. The location, geographic coordinates activities that can be done, description of the attraction, photographs, among other data that served for the elaboration of the parish guide. In the same way, it was applied the registration cards of tourist services with the information of the establishments of hosting and feeding with Zumbahua parish has, with the data of the cards an inventory of these tourist establishments was made counting thus with 19 establishments among hotels, hostels, inns, cabins, restaurants and cafeterias. Once the results of the field trips have been obtained, we proceed to design the tourist guide of the Zumbahua parish, which will be a tourist dissemination material. This guide will include an exhibition of unique photographs and essential information of each attraction in order to generate interest in the user that without a doubt to witness this material will be the next visitor of this parish. The tourist guide will be an essential contribution in the development of the tourist activity in the parish since through the use of this material it is intended to generate greater influx of tourists in the parish and its communities.